EFFECTS OF NPK FERTILIZER AND SPACING ON THE GROWTH PARAMETERS OF OKRO (Abelmoschus esculentus L.) - Danmaigoro, O.; Bilyaminu, A. S.; Abduljalal, T.; Umar, M. M. (FUDMA Journal of Sciences, 2022)
Field trials were conducted during rainy seasons in 2018 and 2019   at Federal, University Dutse Teaching and Research Farm in the Northern Sudan Savanna ecological zone of Nigeria. To evaluate effect of NPK fertilizer and spacing on the growth and yield of okro. The experiment consists of three levels of NPK fertilizer (30, 60 and 120 kg/ha) and three spacing (10, 15 and 20 cm). The treatments combination was laid out in randomized complete block design replicated three times. The results revealed that significant effect of NPK fertilizer on plant height, number of branches, more number of primary branches plant fruit length and number of pod per plant. The various spacing resulted in significant taller plant, more number of leaves, longer length of fruit and higher number of seed per pod. In conclusion, application of 120 kg/ha and spacing at 20 cm gave the best result.
Keywords: Okro, plant height, number of branches, number of pod per plant